Cuckoo - Felker-Martin, Gretchen (Nightfire, Tor Publishing Group, 2024)
"From Gretchen Felker-Martin, the acclaimed author of Manhunt, comes a vicious new novel about a group of teens who must stay true to themselves while in a conversion camp from hell. "A soaring, boundless ode to queer survival. It's flat-out mesmerizing."-Paul Tremblay, author of The Pallbearers. Club Something evil is buried deep in the desert. It wants your body. It wears your skin. In the summer of 1995, seven queer kids abandoned by their parents at a remote conversion camp came face to face with it. They survived-but at Camp Resolution, everybody leaves a different person. Sixteen years later, only the scarred and broken survivors of that terrible summer can put an end to the horror before it's too late. The fate of the world depends on it. "Tense and frighteningly visceral, Cuckoo is a masterwork of body horror thrumming with high octane viciousness." -Eric LaRocca, author of Things Have Gotten Worse Since We Last Spoke Also by Gretchen Felker-Martin: Manhunt"--